Assessing and understanding the generation and function of RNA decay intermediates in non-insect borne flaviviruses - Mundell, Cary T., author; Wilusz, Jeffrey, advisor; Geiss, Brian, committee member; Perera, Rushika, committee member; Reddy, Anireddy, committee member (Colorado State University. Libraries, 2019)
Cellular gene expression is an intricate process regulated on many levels that allows the cell to react correctly to stimuli or to maintain homeostasis. RNA viruses must act to preferentially drive production of their own messenger RNAs (mRNAs) and proteins in order to successfully replicate and ensure continued infection. Due to the necessity for RNA viruses to remain in the cytoplasm, regulatory factors that affect host mRNAs likely also affect the transcripts of RNA viruses. RNA decay represents a major pathway of regulation for mRNAs. A multitude of RNA viruses possess unique mechanisms that act to prevent the decay of viral transcripts and allow for successful translation. Members of the viral family Flaviviridae are positive sense, single-stranded RNA viruses that do not possess a poly(A) tail. Therefore, it is highly likely that these transcripts would be marked as deadenylated and shuttled down one of the RNA decay pathways that exist in the cell. Interestingly, members of the genera Flavivirus of the family Flaviviridae possess a conserved structured 3' untranslated region (UTR) that acts to interfere with the decay processes of the major cytoplasmic cellular 5'-3' decay enzyme XRN1. In addition, members of the generas Hepacivirus, Hepatitis C Virus (HCV) and Pestivirus, Bovine Viral Diarrhea Virus (BVDV), possess XRN1 stalling elements within their 5' UTRs. These stalling sites block the action of the exonuclease and generate decay intermediates. The generation of these decay intermediates represses XRN1 activity in the infected cell. Herein we demonstrate a new method for studying RNA decay through the use of XRN1-resistant RNAs (xrRNAs). In this method we utilize the well characterized xrRNA of Dengue Virus Type 2 (DENV2) as a readout to study the decay rates of relatively large RNA constructs. We show that not only is utilizing an xrRNA an effective method for confirming XRN1-mediated decay, but that the accumulation of the readout xrRNA can be utilized to understand changes in the decay kinetics of RNA substrates. We further utilize this method to demonstrate a lack of XRN1 stalling elements within the poliovirus internal ribosomal entry site (IRES) element. We provide evidence that the stalling of XRN1 in the 5' UTR of BVDV is dependent on both the presence of the entire IRES structure and the presence of a stem loop 5' to the IRES element through the analysis of a series of truncations. Finally, we demonstrate one possible role for the HCV and BVDV decay intermediates as the truncated IRES element maintains translatability in an in vitro system. Collectively, these data better define the structural requirements for the novel XRN1 stalling elements located in the 5' UTR of non-insect borne members of the Flaviviridae as well as the potential function of the decay intermediates.
Keywords: RNA biology; XRN1; virology; flaviviruses